El engagement y la intencion de rotacion laboral de los colaboradores del área registral de la Superintendencia Nacional de los Registros Públicos sede Iquitos agosto 2021 - Carranza Borges, Luis Enrique (2022)
The research on Engagement and the intention of labor rotation in the collaborators of the registry area of the National Superintendence of Public Registries, Iquitos headquarters, August 2021, has as a general objective to determine the relationship between the Engagement and intention to rotate of the employees of the Area. Registry of the National Superintendency of Public Registries Registry Zone No. IV Iquitos Headquarters, August 2021, the research is of a correlational level and a non-experimental design of a transactional nature, the population is made up of 72 collaborators from the Registry Area of the National Superintendence of the Public Registries Registry Zone No. IV Headquarters Iquitos August 2021; In the study period, it was determined that the level of Engagement is 34.7% at the high level, 59.7% at the average level and 5.6% at the low level; in the intention to rotate dimension, the high level is 31.9%, in the regular level 40.3% and low level in 24.8%. Regarding the correlation between the two variables, a correlation coefficient of Rho Spearman of 0.280 and p = 0.017 was obtained, which shows that there is a low significant correlation between engagement and the intention of rotation in the collaborators of the registry area of the National Superintendence of Public Registries Zonal Registral No. IV headquarters Iquitos, August 2021.